2008
DOI: 10.1071/sh07051
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk practices sought by men who have sex with other men, and who use internet websites to identify potential sexual partners

Abstract: Men who have sex with men (MSM) account for the largest number of persons diagnosed with AIDS in the USA, with higher than average rates of drug use and unprotected sex being cited as the principal reasons underlying their high rates of HIV infection. Recent evidence has suggested that the use of websites specifically designed to promote unsafe sexual practices may be particularly common among MSM, thereby fostering their risky behaviours. In light of these findings, the present study is based on a content ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
(32 reference statements)
2
19
1
1
Order By: Relevance
“…Our study showed that the Internet was the most common venue for Chinese MSM to seek male sexual partners, consistent with findings from previous studies that online AIDS Behav sex-finding has become the predominant mode among MSM in China, as in other countries [15,16,[28][29][30]. China has been experiencing vast economic and information technology developments in the past decades, allowing an unprecedented number of people to get access to Internet [28].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the Internet was the most common venue for Chinese MSM to seek male sexual partners, consistent with findings from previous studies that online AIDS Behav sex-finding has become the predominant mode among MSM in China, as in other countries [15,16,[28][29][30]. China has been experiencing vast economic and information technology developments in the past decades, allowing an unprecedented number of people to get access to Internet [28].…”
Section: Discussionsupporting
confidence: 93%
“…Na literatura internacional, estudos que coletaram dados na internet e em locais de sociabilidade gay também encontraram associações similares 1,2,5,7,[17][18][19][20][21][22][23][24][25][26]29,30 . Alguns desses estudos compararam grupos de HSH soropositivo e negativo para HIV, analisando o sexo anal insertivo sem o uso do preservativo e sexo com parceiro sorodiscordante, e nestes estudos, o grupo que recruta parceiros sexuais na internet apresentou maior risco de envolvimento em práticas sexuais desprotegidas [5][6][7]23,26 .…”
Section: Discussionunclassified
“…In 2011 a total of 217 static advertisements appearing on a popular, US-based, racially-diverse sex-seeking website for men who have sex with men (Wohlfeiler et al 2011) were subjected to content analysis (Riff, Lacy, and Fico 2005; Neuendorf 2002; Feliciano, Robnett, and Komaie 2009; Phua and Kaufman 2003; Krippendorff 2004; Klein 2008; Hatala and Prehodka 1996; Downing et al 2013). Eligibility for inclusion: all advertisements containing people and featuring sexually explicit imagery in which a sexual act or genitals were depicted.…”
Section: Methodsmentioning
confidence: 99%
“…In creating the codebook, similar codes were grouped together, duplicate codes were collapsed and new codes were added for content that was not otherwise captured by existing codes. Themes and behaviors documented in prior research (Bull and McFarlene 2000; Paul, Ayala, and Choi 2010; Wilson et al 2009; Klein 2008) and those cited as possible interests in the profiles of men using the site (e.g. “daddies,” “college,” “bears,” etc.)…”
Section: Methodsmentioning
confidence: 99%